A Risk Score Based on 5 Clinico-Pathological Variables Predicts Recurrence of Atypical Meningiomas. Issue 5 (26th February 2020) - Fioravanzo, Adele; Caffo, Maria; Di Bonaventura, Rina; Gardiman, Marina Paola; Ghimenton, Claudio; Ius, Tamara; Maffeis, Valeria; Martini, Maurizio; Nicolato, Antonio; Pallini, Roberto; Pegolo, Enrico; Pinna, Giampietro; et al.
Abstract: The use of adjuvant radiotherapy is controversial in patients with atypical meningiomas treated with gross total resection (GTR). This study aimed to determine whether clinico-pathological features could be helpful to predict the recurrence risk in this group of patients and to identify high-risk ones who could benefit from adjuvant treatment. We collected 200 patients with primary atypical meningiomas treated with GTR but with no adjuvant radiotherapy from 5 different centers. A risk score, formulated by assigning 1 point for the presence and 0 points for the absence of 5 high-risk parameters (male sex, parasagittal site, Simpson grade 3, mitotic index ≥ 6/10 HPF, and sheeting), was the most significant predictor of recurrence. A score ≥2 was associated with 4.7 risk of shorter disease-free survival (p < 0.0001). Our findings indicate that the presence of at least 2 clinico-pathological high-risk factors predicts recurrence of totally resected primary atypical meningiomas and could be helpful for identifying patients who could benefit from adjuvant radiotherapy.